Constraining landscape history and glacial erosivity using paired cosmogenic nuclides in upernavik, northwest greenland - Corbett,LB; Bierman,PR; Graly,JA; Neumann,TA; Rood,DH (Bulletin of the Geological Society of America, 2013)
High-latitude landscape evolution processes have the potential to preserve old, relict surfaces through burial by cold-based, nonerosive glacial ice. To investigate landscape history and age in the high Arctic, we analyzed in situ cosmogenic 10Be and 26Al in 33 rocks from Upernavik, northwest Greenland. We sampled adjacent bedrock-boulder pairs along a 100 km transect at elevations up to 1000 m above sea level. Bedrock samples gave significantly older apparent exposure ages than corresponding boulder samples, and minimum limiting ages increased with elevation. Two-isotope calculations (26Al/10Be) on 20 of the 33 samples yielded minimum limiting exposure durations up to 112 k.y., minimum limiting burial durations up to 900 k.y., and minimum limiting total histories up to 990 k.y. The prevalence of 10Be and 26Al inherited from previous periods of exposure, especially in bedrock samples at high elevation, indicates that these areas record long and complex surface exposure histories, including significant periods of burial with little subglacial erosion. The long total histories suggest that these highelevation surfaces were largely preserved beneath cold-based, nonerosive ice or snowfields for at least the latter half of the Quaternary. Because of high concentrations of inherited nuclides, only the six youngest boulder samples appear to record the timing of ice retreat. These six samples suggest deglaciation of the Upernavik coast at 11.3 ± 0.5 ka (average ± 1 standard deviation). There is no difference in deglaciation age along the 100 km sample transect, indicating that the ice-marginal position retreated rapidly at rates of ~120 m yr-1. © 2013 Geological Society of America.